Uterine Activity: What You Don't Know Can Hurt You. Issue 3 (May 2018) - Miller, Lisa A.
Abstract : There has been a lot of attention to fetal heart rate tracing interpretation during labor in clinical practice and in the literature. Our guest columnist and expert on perinatal patient safety, Lisa Miller, suggests we need to give uterine activity assessment the same level of attention and accuracy to promote safe care for women during labor and to decrease risk of professional liability.